Estudo da incorporação de resíduo industrial polimérico ao CAP - Lima, Cristian Kelly Morais de (2008)
This work presents the incorporation of an industrial polymeric waste into a petroleum asphalt cement with penetration grade 50-60 (CAP 50-60). The main goal of this research is the development of a polymer-modified asphalt, with improvements in its physical properties, in order to obtain a more resistant material to the traffic loads. Furthermore, the use of this polymeric waste will result in economic and environmental benefits. The CAP 50-60 used in this research was kindly supplied by LUBNOR Lubrificantes e Derivados de Petróleo do Nordeste (produced in Fazenda Belém Aracati - Ceará) and the industrial polymeric waste was provided by a button manufacturer industry, located in Rio Grande do Norte state. This polymeric waste represents an environmental problem due to its difficulty in recycling and disposal, being necessary the payment by the industry to a landfill. The difficulty in its reuse is for being this material a termofixed polymer, as a result, the button chips resulting from the molding process cannot be employed for the same purpose. The first step in this research was the characterization of the polymeric waste, using Differential Scanning Calorimetry (DSC) Infrared spectroscopy (IR spectroscopy), and Thermogravimetric analysis (TGA). Based on the results, the material was classified as unsaturated polyester. After, laboratory experiments were accomplished seeking to incorporate the polymeric waste into the asphalt binder according to a 23 experimental factorial design, using as main factors: the polymer content (2%, 7% and 14%), the temperature of the mixture (140 and 180 oC) and the reaction time (20 and 60 minutes). The characterization of the polymer-modified asphalt was accomplished by traditional tests, such as: penetration, ring and ball softening point, viscosity, ductility and flash point temperature. The obtained results demonstrated that the addition of the polymeric waste into the asphalt binder modified some of its physical properties. However, this addition can be considered as a feasible alternative for the use of the polymeric waste, which is a serious environmental and technological problem.